Malorie : a Bird Box novel - Malerman, Josh (Malerman, Josh. Bird box ;, 2020)
"In the thrilling sequel to Bird Box, the inspiration for the record-breaking Netflix film that starred Sandra Bullock and "absolutely riveted" Stephen King, New York Times bestselling author Josh Malerman brings unseen horrors to life. The film adaptation of Malerman's first novel, Bird Box, was watched by over forty-five million Netflix accounts in the first week, the best first seven days ever for a film on the platform. Countless more came to know the story through social media. The image of Sandra Bullock's character, Malorie, blindfolded--as she's led through a terrifying near-future apocalypse by the trained ears of her children--has become synonymous with a new generation of horror. Now from the mind of a true master of suspense comes the next chapter in the riveting tale. This time, Malorie is front and center, and she will confront the dangers of her world head-on"--